Let me out : unlock your creative mind and bring your ideas to life - Himmelman, Peter (Highbridge Audio, 2016)
"Are you afraid of your dreams? Do you want to stop procrastinating? Would you love to be more creative? Is there an idea you need to realize? If so, then Let Me Out is for you. Whether it's learning ragtime piano, losing 30 pounds, or starting an organic jellybean company, award-winning musician turned communications expert Peter Himmelman's unique techniques to harness fear and take the steps to make goals a reality will give you the tools and confidence you need to stop listening to the negative thoughts holding you back and achieve professional and personal success. Using science-based techniques plus methods designed to unlock creative potential (mined from his years as a successful musician) Himmelman shows you how to open your mind and unite left AND right-brained thinking in order to take action through powerful and deceptively simple exercises that will enable you to: -Create more fearlessly, whether it's an ad campaign, a song, or a new business -Communicate more effectively -Finish projects that have stayed in the "bits and pieces" phase forever -Make your ideas take shape in the real world"--